Integrated safety and efficacy among patients receiving Benralizumab for Up to 5 Years - Korn, Stephanie; Bourdin, Arnaud; Chupp, Geoffrey; Cosio, Borja G.; Arbetter, Doug; Shah, Mihir; Gil, Esther Garcia (The journal of allergy and clinical immunology. In practice, 2021)
Background - Benralizumab is an IL-5Rα-directed monoclonal antibody indicated for patients with severe, uncontrolled eosinophilic asthma. - Objective - To evaluate the long-term safety and tolerability of benralizumab among adults treated for up to 5 years. - Methods - This analysis included adults treated with placebo or subcutaneous benralizumab 30 mg every 4 or 8 weeks in the 48-week SIROCCO, 56-week CALIMA, and 28-week ZONDA pivotal trials, who were subsequently enrolled in the 56-week double-blind BORA extension and continued assigned regimens or initiated benralizumab (if previously on placebo) for 16 to 40 weeks, before entering the open-label MELTEMI extension. Safety was measured by adverse and serious adverse event rates. Exacerbations were evaluated in patients with blood eosinophils greater than or equal to 300 cells/μL receiving high-dose inhaled corticosteroids at baseline. - Results - Overall, 446 received treatment and 384 (86.1%) completed the study; 157 (35.2%) received benralizumab for 4 or more years. Adverse and serious adverse event rates (28.5-32.4 and 6.3-8.4 per 100 patient-years, respectively) were low, stable over time, and did not increase with exposure; few (n = 8) discontinued because of adverse events. Serious infections and hypersensitivity event rates were consistent with those in previous studies. Among patients with blood eosinophils greater than or equal to 300 cells/μL-high-dosage inhaled corticosteroids receiving benralizumab every 8 weeks, at least 75% had zero exacerbations annually during the integrated analysis period. - Conclusions - In patients with severe, uncontrolled eosinophilic asthma, long-term benralizumab was safe and well tolerated for up to 5 years. There were no new safety signals, and exacerbations were eliminated in similar percentages of patients as in predecessor studies.